Advancing equity and diversity in engineering education through community based participatory research: study protocol for promoting student mental health, engagement, and motivation - Santana, Carmen Lucia Albuquerque de; Wallerstein, Nina; Libonati Boldi, Lucas Ferreira; Braga, Olivia Ramos Morais; Kurokawa, Fernando Akira; Lotufo Neto, Francisco; Seabra, Antonio Carlos (Frontiers in Education, 2025)
BackgroundEngineering students face growing mental health challenges driven by heavy workloads, competitive assessment, and a culture that normalizes stress. These vulnerabilities are compounded by structural inequalities disproportionately affecting women, marginalized racial and ethnic groups, first-generation students, and those from lower socioeconomic backgrounds. The intersection of academic pressure with social inequities amplifies dropout risks and undermines diversity in higher education. At the Polytechnic School of the University of São Paulo, ongoing curricular reforms and the growing presence of affirmative-action students from national inclusion policies offer a unique opportunity to transform institutional culture and examine these dynamics in depth.MethodsThis protocol outlines a four-year longitudinal, two-cohort study investigating how individual, contextual, and institutional factors—including intersectionality, affirmative action, and curricular reforms—affect engineering students’ mental health, motivation, and engagement. Grounded in Community-Based Participatory Research, Bronfenbrenner’s Bioecological Model, and Self-Determination Theory, the study assesses the impact of institutional reforms aligned with national policies, identifies barriers and facilitators to equity, and co-develops actionable recommendations to transform academic practices and policy. A mixed-methods, multiphase design will collect surveys and data for all students entering from 2025 to 2028 (3,480 students). Two 2025 cohorts from distinct curricular models will be followed longitudinally, with no study-based selection and proportional representation of affirmative-action, gender, and sociodemographic groups. Qualitative activities will also engage 20 faculty, alongside students; quantitative data will be analyzed with descriptive and longitudinal models, and qualitative data will undergo thematic coding. Participatory processes ensure collaborative data interpretation and co-design of a mental-health promotion intervention with students, faculty, and staff within the research-governance structure.DiscussionThe study will illuminate how institutional, individual, and contextual factors intersect to shape students’ well-being and academic experiences. Findings are expected to reveal structural barriers, protective factors, and effects of curricular reforms and affirmative-action policies. Its participatory, systemic approach offers a model for other university settings—including public and population health—showing pathways to foster culture change and co-create evidence-based policies that promote well-being and equity. The study also seeks to strengthen students’ capacity to apply these principles in their future practice.Clinical trial registrationOpen Science Framework (OSF), DOI 10.17605/OSF.IO/N43TD.